PREDIKSI OPTIMASI DIMENSI BALOK KOLOM BANGUNAN MASJID DENGAN METODE ARTIFIAL NEURAL NETWORK: indonesia - Jauhari Prasetiawan (J-ENSITEC, 2022)
Indonesia is the confluence of three of the world's major plates, therefore a lot of plate activity occurs so that earthquake intensity often occurs. The earthquake resulted in many casualties, this is because many building structures do not meet the requirements of earthquake-resistant buildings. The structure of mosque buildings in Lombok has many towering mosque towers. Many mosque buildings in Lombok do not apply the earthquake-resistant building principle, namely strong column weak beam, so that the average mosque building collapses is the soft story type. The research method used to optimize the dimensions of the columnar beam in this study there are two methods, namely optimization using SAP 2000 and then optimization using Artificial Neural Network (ANN) modeling. The empirical equations obtained are three equations, namely the equation of a beam, a square column and a circle column. The percentage of error that occurs in the use of the empirical formula is 0.88%, so that the equation can be used to perform dimensional prediction calculations with different variations.